(untitled) (Proceedings of International Conference on Special Education, 2015)
Sensory integration theory was developed to explain neurological processing of sensory information. The theory is based on the understanding that interferences in neurological processing of sensory information interrupt the construction of appropriate behaviours. Children with particular conditions, including Autism Spectrum Disorder (ASD), can have difficulties generating appropriate behaviours in response to the sensory stimuli they perceive and their environment. These difficulties impact on the educational experiences of these children. The aim of this study is to develop a sensory integration intervention programme to address behavioural problems for children with ASD and to report on the practicality of the programme with an aim for implementing it in a randomised controlled trial. The intervention programme was developed through a comprehensive literature review and expert panel review. Three children diagnosed with ASD aged between 6-12 years old with normal to moderate intellectual quotient received the intervention. Six outcome measures were administered before and after the intervention. The outcomes included parent self-rated and therapist-assessed behaviour, school function, daily living skills and social participation. Interview with parents were also conducted after the intervention to collect their feedback on the programme. All participants reported an improvement after post intervention mostly in communication, socialization, reduction of behaviour problems and reduction of sensory problems. The result of this study supported the use of Sensory Integration intervention to enhance children with ASD’s positive behaviours to allow them to learn, socialise and engage into appropriate daily functioning.